2021
DOI: 10.3389/fpls.2021.786309
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Salinity, Temperature, and Drought Stress in Grafted Watermelon Seedlings Using Chlorophyll Fluorescence

Abstract: Chlorophyll fluorescence (CF) is used to measure the physiological status of plants affected by biotic and abiotic stresses. Therefore, we aimed to identify the changes in CF parameters in grafted watermelon seedlings exposed to salt, drought, and high and low temperatures. Grafted watermelon seedlings at the true three-leaf stage were subjected to salinity levels (0, 50, 100, 150, and 200 mM) and temperature [low (8°C), moderate (24°C), and high (40°C)] stresses for 12 days under controlled environmental cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 82 publications
2
9
0
1
Order By: Relevance
“…The observed decrease in F M and F M ´ found at 3 M NaCl in Klebsormidium and Stigeoclonium is a well-known phenomenon found in previous salinity studies in cyanobacteria (Lu and Vonshak 2002), microalgae (Liang et al 2014) and vascular plants (e.g., Hniličková et al 2017, Oláh et al 2021. Rfd, which is considered an indicator of plant vitality under stressful con-ditions, decreased at the highest salinity level (3M NaCl) as well, in accordance with Shin et al (2020Shin et al ( , 2021, who also found a significant decrease in Rfd levels in plants exposed to the extreme salinity stress.…”
Section: Discussionsupporting
confidence: 77%
“…The observed decrease in F M and F M ´ found at 3 M NaCl in Klebsormidium and Stigeoclonium is a well-known phenomenon found in previous salinity studies in cyanobacteria (Lu and Vonshak 2002), microalgae (Liang et al 2014) and vascular plants (e.g., Hniličková et al 2017, Oláh et al 2021. Rfd, which is considered an indicator of plant vitality under stressful con-ditions, decreased at the highest salinity level (3M NaCl) as well, in accordance with Shin et al (2020Shin et al ( , 2021, who also found a significant decrease in Rfd levels in plants exposed to the extreme salinity stress.…”
Section: Discussionsupporting
confidence: 77%
“…This was repeated until the flower bud differentiation was completed in the low temperature environment. In the low temperature environment, the trend of NPQ is consistent with Rfd (Shin et al, 2021), therefore, the NPQ curve of L. chinense var. rubrum under low temperature treatment has a similar trend to the Rfd curve.…”
Section: Discussionsupporting
confidence: 54%
“…The efficiency of photosynthesis in the plant is reduced. Salinity decreased the chlorophyll content [19][20][21][22] . Salt reduces the resistance of the mesophyll 23 .…”
Section: Discussionmentioning
confidence: 97%